(untitled) (Research, Society and Development, 2020)
Objective: To identify the prevalence of the use of artificial milk in newborns treated in a university extension project; analyze the indications for the use of artificial milk; discuss the care actions necessary to encourage, support and promote breastfeeding that apply to the indications found for use of artificial milk. Methodology: Quantitative, exploratory, descriptive study, conducted from September 2015 to November 2016, through the analysis of the records of previous care on breastfeeding and the medical records of 137 binomials admitted to a public hospital located in the city of Rio de Janeiro/RJ. The organization and analysis were performed using Excel software, with the theoretical basis of articles and recommendations manuals from the Ministry of Health, the Pan American Health Organization and the World Health Organization. Research approved by the Research Ethics Committee of the Federal State University of Rio de Janeiro, under No. 1,241,895. Results: Twenty-eight newborns were detected using milk formula with no HIV-positive impediment, in an Intermediate Unit or Intensive Care Unit. The prevalence of complement use was 20.43%. The reasons for the indications were: 10.71% maternal conditions; 10.71% without HIV serology; 64.28% conditions of the newborn; and 14.28% due to other conditions. It was observed that, in some cases, the use of artificial milk would be avoidable if the intervention, in the orientation and early detection of problems, was more intense. Conclusion: With the identification of problems in a timely manner, a care plan can be drawn up to prevent the use of artificial milk.